BOOK REVIEWS (Heythrop journal, 1990)
John Henry Newman: A Biography. By Ian Ker. Pp.xiii, 762, Oxford, Clarendon Press, 1988, £48.00. Cassirer: Symbolic Forms and History. By John Michael Krois. Pp.xvii, 262, New Haven, Yale University Press, 1987, £29.95. Gadamer: Hermeneutics, Tradition and Reason. By Georgia Warnke. Pp.xii, 206, Oxford, Polity Press, 1987, £7.95. Licensed Insanities: Religions and Belief in God in the Contemporary World. By John Bowker. Pp.ix, 164, Darton Longman and Todd, 1987, £8.95. The Canon of the New Testament: Its Origin, Development and Significance. By Bruce M. Metzger. Pp.x, 326, Oxford, Clarendon Press, 1987, £30.00. The Gnostic Scriptures: A New Translation with Annotations and Introductions. By Bentley Layton. Pp.xlii, 526, London, SCM Press, 1987, £25.00. Women and Early Christianity: Are the Feminist Scholars Right? By Susanne Heine. Pp.vi, 182, London, SCM Press, 1987, £6.95. Eunomius, The Extant Works (Oxford Early Christian Texts). Text and translation by Richard Paul Vaggione. Pp.xvii, 209, Oxford, Clarendon Press, 1987, £30. The Formation of a Persecuting Society: Power and Deviance in Western Europe, 950–1250. By R.I. Moore. Pp.viii, 168, Oxford, Basil Blackwell, 1987, £19.50. Charity and Community in Medieval Cambridge (Cambridge Studies in Medieval Life and Thought 4). By Miri Rubin. Pp.xiv, 365, Cambridge University Press, 1987, £30. Representatives of the Lower Clergy in Parliament, 1295–1340 (Royal Historical Society. Studies in History 50). By Jeffrey H. Denton and John P. Dooley. Pp.142, Woodbridge, The Boydell Press, 1987, £25.00. From Ockham to Wyclif (Studies in Church History Subsidia 5). Edited by Anne Hudson and Michael Wilks. Pp.xv, 486, Oxford, Basil Blackwell, 1987, £35.00 Literary and Educational Writings (Collected Works of Erasmus 27 and 28). Edited by A.H.T. Levi. Pp.xxx, 638, Toronto, University of Toronto Press, 1986, £65.00. Paraphrase on Mark (Collected Works of Erasmus 49). Edited by Erika Rummel. Pp.xiv, 235, Toronto, University of Toronto Press, 1988, £28.00 The Dawn of the Reformation. Essays in Late Medieval and Early Reformation Thought. By Heiko A. Oberman. Pp.x, 309, Edinburgh, T. & T. Clark, 1987. £14.95. The Intellectual Origins of the European Reformation. By Alister McGrath. Pp.viii.223, Oxford, Basil Blackwell, 1987, £25.00. The English Reformation Revised. Edited by Christopher Haigh. Pp.x, 229, Cambridge University Press, 1987, £8.95. Das Papstamt im Disput zwischen Lutheranern und Katholiken: Schwerpunkte von der Reformation bis zur Geganwart (Innsbrucker Theologische Studien 20). By Wolfgang Klausnitzer. Pp.586, Innsbruck, Tyrolia Verlag, 1987, DM 112. The Chronicle of the Hutterian Brethren. Volume I. Translated and edited by the Hutterian Brethren. Pp.ixxv, 887, Rifton (N.Y.), Plough Publishing House, 1987, no price given. Cardinal de La Rochefoucauld: Leadership and Reform in the French Church. By Joseph Bergin. Pp.viii, 302, New Haven and London, Yale University Press, 1987, £25.00 A Guide for Preachers on Composing and Delivering Sermons. The ‘Or ha-Darshanim’ of Jacob Zahalon. A Seventeenth-Century Italian Preacher's Manual (Moreshet Series, Studies in Jewish History, Literature and Thought XI). By Henry Adler Sosland. Pp.xiv, 194, 54*, New York, The Jewish Theological Seminary of America, 1987, $20.00. Jewish-Christian Relations in the Seventeenth Century. Studies and Documents (International Archives of the History of Ideas 119). Edited by J. van den Berg and Ernestine G.E. van der Wall. Pp.ix, 210, Dordrecht, Kluwer Academic Publishers, 1988, £46.95. The Life of James Sharp, Archbishop of St Andrews, 1618–1679: A Political Biography. By Julia Buckroyd. Pp.ix, 150, Edinburgh, John Donald, 1987, £18.00 Joachim of Fiore and the Myth of the Eternal Evangel in the Nineteenth Century. By Marjorie Reeves and Warwick Gould. Pp.x, 365, Oxford University Press, 1987, £35.00 Religion in England, 1688–1791 (Oxford History of the Christian Church). By Ernest Gordon Rupp. Pp.xiii, 584, Oxford, Clarendon Press, 1986, £45.00. Liberal Anglican Politics: Whiggery, Religion and Reform, 1830–1841. By Richard Brent. Pp.xii, 340, Oxford, Clarendon Press, 1987, £32.50. The Victorian Christian Socialists. By Edward Norman, Pp.201, Cambridge University Press, 1987, £17.50 Tradition Renewed: The Oxford Movement Conference Papers. Edited by Geoffrey Rowell. Pp.xvi, 237. London, Darton, Longman and Todd, 1986, £12.95. A Circle of Friends: The Tennysons and the Lushingtons of Park House. By John O. Waller. Pp.xvi, 290, Columbus, Ohio State University Press, 1986, $29.50. Democracy and Religion: Gladstone and the Liberal Party, 1867–1875 (Cambridge Studies in the History and Theory of Politics). By J.P. Parry. Pp.xiii, 504, Cambridge University Press, 1986, £37.50. The Household of Faith: Roman Catholic Devotions in Mid-Nineteenth-Century America (Notre Dame Studies in American Catholicism). By Ann Taves. Pp.x, 197, Notre Dame, Indiana, University of Notre Dame Press, 1986, $17.95. The American Catholic Parish: A History from 1850 to the Present. Edited by Jay P. Dolan. 2 vols. Mahwah, New Jersey, Paulist Press, 1987, $24.95 each. Amigo.-Friend of the Poor, Bishop of Southwark, 1904–1949. By Michael Clifton. Pp.236, Leominster, Fowler Wright, 1987, £9.95. American Catholic Religious Thought: The Shaping of a Theological and Social Tradition. Edited by Patrick W. Carey. Pp.iv, 302, New York, Paulist Press, 1987. $10.95 Altered Landscapes: Christianity in America, 1935–1985: Essays in Honor of Robert T, Handy. Edited by David W. Lotz, Donald Shriver and John F. Wilson. Pp.xi, 387, Grand Rapids, W.B. Eerdmans, 1989, $27.50/$17.95. Doctrines of Religious Communities. A Philosophical Study. By William A. Christian, Sr. Pp.vii, 234, New Haven & London, Yale University Press, 1987, £22.50. Continental Philosophy and Modern Theology. By David Brown. Pp.xii, 250, Oxford, Basil Blackwell, 1987, £27.00. The Structure of Emotions. By Robert M. Gordon. Pp.xiv, 161, Cambridge University Press, 1987, £22.50. Philosophical Perspectives on Developmental Psychology. Edited by James Russell. Pp.ix, 262, Oxford, Basil Blackwell, 1987, £27.50. A Prospectus for the Triumph of Realism. By Thomas A. Russman. Pp.viii, 157, Macon GA, Mercer University Press, 1987, $24.95. Listening to the Cicadas: A Study of Plato's ‘Phaedrus’ (Cambridge Classical Studies). By G.R.F. Ferrari. Pp.xii, 293, Cambridge University Press, 1987, £22.50. Studies in Medieval Philosophy (Studies in Philosophy and the History of Philosophy 17). Edited by John F. Wippel. Pp.viii, 302, Washington DC, Catholic University of America Press, 1987, $36.95. Thomas Buckingham and the Contingency of Futures (University of Notre Dame, The Medieval Institute Publications in Medieval Studies 25). By Bartholomew R. De la Torre. Pp.xii, 394, University of Notre Dame Press, 1987, £35.95. Montesquieu (Past Masters). By Judith N. Shklar. Pp.vii, 136, Oxford University Press, 1987, £11.95/£3.50.